Settling down at Ceibal and Cuello: variation in the transition to sedentism across the Maya lowlands - MacLellan, Jessica (Frontiers in Human Dynamics, 2024)
During the Middle Preclassic period (c. 1000-350 BCE), the people of the Maya lowlands transitioned from a mobile horticulturalist to sedentary farming lifestyle, exemplified by permanent houses arranged around patios and rebuilt over generations. Early evidence of this change has been found in northern Belize, in the Belize Valley, and at Ceibal, Guatemala. At Cuello and other sites in northern Belize, mortuary rituals tied to ancestor veneration created inequality from the beginning of sedentary life. There, relatively dense populations facilitated the emergence of competitive sociopolitical strategies. However, Maya communities in different regions adopted different aspects of sedentism at different times and employed different power strategies. Unlike Cuello, Ceibal was founded as a ceremonial center by semi-mobile people. Middle Preclassic ritual practices at Ceibal and in the Belize Valley were associated with more collective leadership. At the end of this period, increased population densities contributed to a shift to more exclusionary rituals and political strategies throughout the lowlands.